A Response Surface Methodology Approach to Investigate the Effect of Sulfur Dioxide, pH, and Ethanol on DbCD and DbVPR Gene Expression and on the Volatile Phenol Production in Dekkera/Brettanomyces bruxellensis CBS2499 - Valdetara, Federica; Fracassetti, Daniela; Campanello, Alessia; Costa, Carlo; Foschino, Roberto; Compagno, Concetta; Vigentini, Ileana (Frontiers in Microbiology, 2017)
Dekkera/Brettanomyces bruxellensis, the main spoilage yeast in barrel-aged wine, metabolize hydroxycinnamic acids into off-flavours, namely ethylphenols. Recently, both the enzymes involved in this transformation, the cinnamate decarboxylase (DbCD) and the vinylphenol reductase (DbVPR), have been identified. To counteract microbial proliferation in wine, sulphur dioxide (SO2) is used commonly to stabilize the final product, but limiting its use is advised to preserve human health and boost sustainability in winemaking. In the present study, the influence of SO2 was investigated in relation with pH and ethanol factors on the expression of DbCD and DbVPR genes and volatile phenol production in D. bruxellensis CBS2499 strain under different model wines throughout a Response Surface Methodology. In order to ensure an exact quantification of DbCD and DbVPR expression, an appropriate housekeeping gene was sought among DbPDC, DbALD, DbTEF, DbACT and DbTUB genes by GeNorm and Normfinder algorithms. The latter gene showed the highest expression stability and it was chosen as the reference housekeeping gene in qPCR assays. Even though SO2 could not be commented as main factor because of its statistical irrelevance on the response of DbCD gene, linear interactions with pH and ethanol concurred to define a significant effect (p <0.05) on its expression. The DbCD gene was generally downregulated respect to a permissive growth condition (0 mg/L mol SO2, pH 4.5 and 5% v/v ethanol); the combination of the factor levels that maximizes its expression (0.83 fold-change) was calculated at 0.25 mg/L mol SO2, pH 4.5 and 12.5% (v/v) ethanol. On the contrary, DbVPR expression was not influenced by main factors or by their interactions; however, its expression is maximized (1.72 fold-change) at the same conditions calculated for DbCD gene. While no linear interaction between factors influenced the off-flavour synthesis, ethanol and pH produced a significant effect as individual factors. The obtained results can be useful to improve the SO2 management at the grape harvesting and during winemaking in order to minimize the D./B. bruxellensis spoilage.